PREDICTING THE BALLISTIC STRENGTH OF ULTRA HIGH MOLECULAR WEIGHT POLYETHYLENE/FIBER COMPOSITES BY IMPLEMENTING FULL FACTORIALEXPERIMENTAL DESIGN - Dimko Dimeski; Vineta Srebrenkoska (Journal of Engineering & Processing Management, 2014)
The purpose of the study is to predict the ballistic strength of hard ultra-high molecular weight polyethylene fiber/phenolicballistic composites by implementing the full factorial experimental design. When designing ballistic composites two major factors are the most important: the ballistic strength and the weight of the protection. The ultimate target is to achieve the required ballistic strength with the lowest possible weight of the protection. The hard ballistic UHMWPE/phenolic composites were made by the open mold high pressure, high-temperature compression of prepreg made of plain woven UHMWPE fiber fabric and polyvinyl butyral modified phenolic resin.The preparation of the composites was done in accordance to the 22 full factorialexperimental design. The areal weight of composites was taken to be the first factor and the second - fiber/resin ratio. The first factor low and high levels are chosen to be 2 kg/m2 and 9 kg/m2, respectfully and for the second factor - 80/20 and 50/50, respectfully. The first-order linear model to approximate the response i.e. the ballistic strength of the composites within the study domain (2 - 9) kg/m2 x (80/20 - 50/50) ratio was used. The influence of each individual factor on the response function is established, as well as the interaction of the two factors. It was found out that the estimated first-degree regression equation with interaction gives a very good approximation of the experimental results of the ballistic strength of composites within the study domain.
Keywords: UHMWPE fiber; ballistic composites; factorial design; regression equation; V50